MEMBANGUN REKOGNISI WARIA MELALUI PONPES AL FATAH YOGYAKARTA 2008-2016 - Lestari, Inda (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2023)
Transvestites in the eyes of society are still seen as deviant and violating norms. Not only from a socio-economic point of view, in worship which should also be the right of all mankind even if it is a transgender it is difficult to obtain. Waria will not be easily accepted to worship in public places of worship such as mosques. They will be shunned when worshiping at the mosque, such as during congregational prayers. Waria will be rejected in both the men's and women's ranks. Even deepening religious knowledge was difficult because they could not participate in general recitation activities. Moved by an inner need to worship, the Yogya transgender group formed the Waria Islamic Boarding School. The aim is to accommodate transgender women to worship and study Islam in greater depth. Waria also often feel confused about how they should worship. In fact, the previous network and visits are still maintained and there are even more visits to the Islamic boarding school. This paper wants to prove that the uniqueness of identity as a transgender can actually be used as a strength. Network is a strength derived from the unique identity, especially their position as a Muslim. This makes Islamic Boarding Schools a unique entity among other transgender organizations in Indonesia and even the world. Al Fatah Waria Islamic Boarding School is the first religious-based transgender organization. Then, from the strength of the network, it can provide recognition and bargaining position for Muslim transvestites to build individual and collective strength.